Impact of Accelerated Carbonation Curing (ACC) on the Properties of Guinea Corn Husk Ash Blended Concrete - Odeyemi, S. O.; Sholagberu, M. S.; Abdulwahab, R.; Adedeji, A. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
There are different methods of curing concrete. These include immersion in water, sprinkling of the concrete samples, curing with sand or sawdust and open-air curing method. However, research on the use of Accelerated Carbonation Curing (ACC) method for curing concrete is very scanty. Therefore, this study concentrates on determining the impact of ACC on the properties of Guinea Corn Husk Ash (GCHA) Blended Concrete. Materials such as Portland Limestone Cement, Guinea Corn Husk Ash (GCHA), sand, and granite dust were tested for fineness, coarseness, specific gravity before they were used for producing the concrete. Characterizations, such as Scanning Electronic Microscopy (SEM), Energy Dispersive X-Ray Fluorescence Spectrometry (EDXRF) and X-Ray Diffraction (XRD) were performed to investigate the properties of the GCHA. The batched concrete was then cured using the ACC and Water Curing (WC) methods. Mix ratios of 0%, 5%, and 10% GCHA were utilized in obtaining the highest compressive strength. Compressive strength for 0%, 5%, 10% incorporation of GCHA in concrete for both ACC and WC methods of curing at 56th day were found to be 23.3 N/mm2 and 24.5 N/mm2; 19.1 N/mm2 and 21.7 N/mm2; 11.1 N/mm2 and 11.8 N/mm2 respectively. The highest sorptivity values were obtained at 10% replacement of cement with GCHA for both ACC and WC cured samples. However, the Sorptivity values decreased as the curing age increases both for ACC and WC cured concrete. This demonstrates that both methods produced durable concrete.